Sodium-ion battery positive electrode material with Mn replaced by Zn and preparation method of sodium-ion battery positive electrode material

By replacing Mn with Zn in spinel sodium manganate positive electrode material, precursor particles with smooth surface and increased specific surface area are prepared, which solves the problem of structural collapse and crystal form distortion of the material during circulation, and significantly improves the stability and cyclic performance of the material.

CN119560552APending Publication Date: 2025-03-04HAIAN CHANGZHOU UNIV HIGH TECH R&D CENT +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411922208.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The spinel nickel sodium manganate positive electrode material is prone to structural collapse and crystal distortion during the cycle, resulting in the infiltration and migration of sodium ions and the reduction of charge and discharge performance.

Method used

A spinel sodium nickel manganate positive electrode material that replaces Mn with Zn is used, and its general structural formula is Li0.5Mn(1.5-x)Ni0.5ZnxO2, 0

Benefits of technology

The stability and circulation performance of the material are improved, the discharge capacity is increased by about 5mAh/g, the first charge and discharge efficiency is about 85%, and the capacity retention rate reaches about 95% after 100 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560552A_ABST
    Figure CN119560552A_ABST
Patent Text Reader

Abstract

The invention relates to a sodium-ion battery positive electrode material with Mn replaced by Zn and a preparation method of the sodium-ion battery positive electrode material, and belongs to the technical field of production of sodium-ion battery positive electrode materials. A carbonate coprecipitation method is adopted, a metal salt solution and a precipitant solution are controlled to react in a base solution to prepare a precursor, and the precursor is calcined to obtain the positive electrode material with the structural formula of Na0. 5Mn (1.5-x) Ni0. 5ZnxO2. The method provides a more powerful support for the material, and improves the stability of the material, so that the performance of the positive electrode material is obviously improved, and the cycle capability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery positive electrode materials, and specifically relates to a sodium battery positive electrode material in which Mn is replaced by Zn, and a preparation method thereof. Background Art

[0002] Spinel nickel sodium manganese oxide positive electrode material has good performance, high capacity, excellent cycle performance and coulomb rate, low cost and good safety, so it has attracted widespread attention. At present, the preparation technology of spinel nickel sodium manganese oxide positive electrode material is becoming more and more mature, and has been widely used in sodium ion power batteries.

[0003] However, there are also some problems. Although spinel sodium nickel manganese oxide positive electrode materials have a higher discharge specific energy, such materials are prone to structural collapse and crystal distortion during the cycle process. The crystal structure is destroyed, the embedding and migration of sodium ions are affected, and the side reactions are also aggravated, resulting in a decrease in its charge and discharge performance, which seriously hinders its development and application. Summary of the invention

[0004] In order to improve the stability of the spinel sodium nickel manganese oxide positive electrode material and improve the problem of crystal structure collapse during the cycle process, the present invention proposes a spinel sodium nickel manganese oxide positive electrode material in which Zn replaces Mn.

[0005] The general structural formula of the spinel sodium nickel manganate positive electrode material in which Zn replaces Mn is: Li 0.5 Mn (1.5-x) Ni 0.5 Zn x O 2 , where 0<x<1.

[0006] Compared with conventional NCM ternary positive electrode materials, the Zn-substituted spinel sodium nickel manganese oxide positive electrode material precursor particle morphology of the present invention has a smoother surface, a larger specific surface area, and good crystallinity. Compared with transition metals, the Zn atomic radius is smaller, and the Zn-substituted sample reduces the interlayer spacing, and the bond energy of the transition metal layer and the oxygen layer is enhanced. At the same time, Zn substitution promotes the grain growth of the spinel sodium nickel manganese oxide positive electrode material, improves the degree of crystallization, leads to an increase in the stress inside the grain, promotes the lattice resonance, and provides a more powerful support for the material. During charging and discharging, the sodium ion transmission is relatively stable, which improves the stability of the material.

[0007] The discharge capacity of the spinel sodium nickel manganese oxide positive electrode material replaced by Zn in the present invention is about 135 mAh / g, and the first charge and discharge efficiency is about 85%. Compared with the general spinel sodium nickel manganese oxide positive electrode material, its capacity is increased by about 5 mAh / g. At the same time, after 100 cycles, its capacity retention rate can reach about 95%, which is significantly improved.

[0008] Another object of the present invention is to provide a method for preparing the above positive electrode material.

[0009] The specific steps are: 1) dissolving nickel salt, manganese salt and zinc salt in deionized water to obtain a mixed metal salt aqueous solution; Dissolve sodium carbonate in deionized water, then add ammonia water to obtain a precipitant solution with a pH value of 7.5-10.5; 2) first adding a base liquid into a reaction container, and then adding the mixed metal salt aqueous solution and the precipitant solution into the reaction container for a co-precipitation reaction; After the reaction is completed, the precipitate and the supernatant are separated, and the precipitate is washed, filtered, dried, and ground to obtain a precursor; 3) The precursor and the sodium salt are uniformly mixed and then calcined. During the calcination, the temperature is first raised to 400-500° C., kept warm for 3 hours, then raised to 700-900° C., kept warm for 8-24 hours, and finally cooled to room temperature to obtain a spinel sodium nickel manganese oxide positive electrode material in which Zn replaces Mn.

[0010] In the preparation method of the present invention, sodium carbonate is used as a main precipitant and ammonia water is used as a complexing agent. By reacting in a bottom liquid, a part of Mn is replaced by Zn to synthesize a spinel sodium nickel manganate positive electrode material. The surface of the prepared precursor particles is smoother and the specific surface area is increased, which is conducive to the formation of a Zn-substituted Mn spinel sodium nickel manganate positive electrode material with a relatively stable crystal structure, which is beneficial to Li + Compared with the spinel sodium nickel manganese oxide positive electrode material prepared by the general method, the material prepared by the present invention is not easy to collapse when compacted, thus significantly improving the performance of the positive electrode material.

[0011] The process flow of the present invention is relatively simple and easy to operate. The discharge capacity of the spinel nickel sodium manganese oxide positive electrode material replaced by Zn is about 135 mAh / g, and the first charge and discharge efficiency is about 85%. Compared with the general spinel nickel sodium manganese oxide positive electrode material, its capacity is increased by about 5 mAh / g. At the same time, after 100 cycles, the capacity retention rate can reach about 95%, which has been significantly improved. The spinel nickel sodium manganese oxide positive electrode material has a smooth surface, an increased specific surface area, good crystallinity, is not easy to collapse when compacted, has a higher tap density, and thus has better cycle performance.

[0012] Furthermore, the total concentration of the metal salts in the mixed metal salt aqueous solution of the present invention is 1 mol / L to 2 mol / L. If the metal salt concentration is too low, the complexation reaction is incomplete; if the concentration is too high, the secondary particles formed are too large. When the concentration of the transition metal salt solution is within the range of 1 mol / L to 2 mol / L, the complexation reaction of metal ions and ammonia can be promoted, which is more beneficial for synthesizing precursors with spherical morphology and narrow particle size.

[0013] The molar numbers of nickel, manganese and zinc ions in the metal salt solution are o, y and 1-oy respectively, and: 0.1<o≤1, 0.1≤y≤1, 0<1-oy≤1, and a complete crystalline spinel structure can be formed under the limited conditions.

[0014] The concentration of the transition metal salt solution has a very important influence on the average particle size and particle size distribution of the secondary particles of the spinel sodium nickel manganese oxide positive electrode material precursor.

[0015] The nickel salt is nickel sulfate, nickel nitrate or nickel acetate; The manganese salt is manganese sulfate, manganese nitrate or manganese acetate; the zinc salt is zinc sulfate, zinc nitrate or zinc acetate.

[0016] Transition metals of sulfates, nitrates, and acetates are easily soluble in water at room temperature, and the solutions are relatively stable at room temperature. In the co-precipitation reaction, the elemental composition of each part is relatively uniform.

[0017] The concentration of sodium carbonate is 1 / 2 of the concentration of metal cations in the metal salt solution. The solubility of carbonate is low and it is easy to precipitate when the concentration is too high.

[0018] During the coprecipitation reaction, the temperature of the reaction system is 40-80° C. The bulk density of the precursor prepared at different reaction temperatures is different. As the temperature increases, the growth rate of the grains increases. However, if the temperature is too high, the kinetic energy of the reactant molecules increases too quickly, which is not conducive to the formation of stable crystal nuclei.

[0019] During the coprecipitation reaction, the stirring speed in the reaction container is 200-800r / min. When the metal salt solution is dripped into the reaction cover, the metal ions first complex with ammonia to form a metal complex, and then slowly release transition metal ions to react with carbonate to generate a large number of primary particle products. After that, these primary particles collide with each other during the stirring process, rotate along the inner wall of the container and slowly agglomerate to form secondary particles. Therefore, a reasonable stirring rate is a necessary condition for synthesizing spherical positive electrode materials with uniform size distribution.

[0020] During the coprecipitation reaction, the metal salt solution is added at a rate of 20 ml / min to 500 ml / min, and the precipitant solution is added at a rate of 20 ml / min to 500 ml / min. In order to make metal ions such as Ni and Mn coprecipitate and crystallize uniformly at the same rate, we can control the pH value by controlling the injection speed of the metal salt solution and the precipitant, so that they can coprecipitate uniformly. At the same time, the injection time also has a great influence on the morphology of the precursor. The size of the secondary particles of the precursor will increase with the increase of the reaction time before reaching a stable value.

[0021] During the reaction, the base liquid is deionized water.

[0022] In addition, the sodium salt required for calcination accounts for 80-120%. When the transition metal layer in the material is less sodium-rich, vacancies will appear in the transition metal layer of the material. Materials containing transition metal layer vacancies will have better reversibility on the 4.7V platform, and the order of Li and Mn will be higher. However, as the charge and discharge cycle proceeds, the order of Li and Mn will gradually decrease during the cycle, causing the discharge specific capacity to increase to a certain extent as the cycle continues. In materials rich in sodium, due to the absence of Ni 3+ To compensate for the lack of cationic potential, oxygen vacancies are generated, which promotes the deoxygenation process during the first charge, allowing the material to release more lithium during the first charge and improve the first charge and discharge capacity.

[0023] In summary, the present invention controls the particle growth by controlling the reaction speed, the addition time, and the concentration of ammonia water, so that most of the particles are relatively uniform spherical particles with a relatively smooth surface and a larger specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the morphology of the nickel-manganese precursor without zinc doping.

[0025] Figure 2 This is the morphology of the synthesized Zn-substituted Mn spinel sodium nickel manganese oxide positive electrode material precursor. DETAILED DESCRIPTION

[0026] 1. Preparation of precursors.

[0027] 1. Prepare metal salt solution: The following nickel salt may be any one of nickel sulfate, nickel nitrate or nickel acetate.

[0028] The following manganese salt is any one of manganese sulfate, manganese nitrate or manganese acetate.

[0029] The following zinc salt is any one of zinc sulfate, zinc nitrate or zinc acetate.

[0030] In this embodiment, sulfate is used to prepare a mixed metal salt solution, and 43.8 g of nickel sulfate hexahydrate, 84.5 g of manganese sulfate monohydrate and 47.9 g of zinc sulfate heptahydrate are weighed respectively, and deionized water is added to prepare a metal salt solution with a concentration of 2 mol / L.

[0031] 2. Prepare precipitant solution: Weigh 106 g of sodium carbonate and add it to 1000 ml of deionized water to prepare a 1 mol / L (sodium carbonate concentration is 1 / 2 of the metal cation concentration in the metal salt solution) sodium carbonate aqueous solution; then add 20 ml of ammonia water to obtain a precipitant solution with a pH value of 7 to 9.

[0032] 3. Preparation process: During the reaction, heating was performed in a water bath at 40-60°C.

[0033] Take 1500 ml of deionized water as the base liquid and add it into the reaction kettle.

[0034] After the temperature in the reactor rises to 40-60° C., stirring is started, and the above metal salt solution and precipitant solution are slowly added dropwise to the bottom liquid to carry out carbonate co-precipitation reaction.

[0035] During the reaction, the stirring speed is 260-500 r / min.

[0036] The dropping speed of the metal salt solution and the precipitant solution can be kept consistent, maintaining an injection speed of 50 ml per minute.

[0037] After the above additions are completed, continue stirring in the reactor and age for 2 to 5 hours.

[0038] Discharge the material, let it stand and settle, and separate the supernatant and the lower sediment.

[0039] The lower precipitate is removed and washed with deionized water for 3 to 5 times, filtered, and the liquid phase is removed and placed in an electric heated air drying oven, dried at 70 to 80° C., and then ground to obtain a precursor.

[0040] 2. Preparation of spinel sodium nickel manganese oxide positive electrode material with Zn replacing Mn.

[0041] 10 g of the precursor was uniformly mixed with 4.56 g (97%) of sodium carbonate, put into a crucible, and calcined in a muffle furnace.

[0042] Calcination temperature: first raise the temperature to 500°C, keep it warm for 3 hours, then raise the temperature to 900°C, keep it warm for 8 hours, and finally cool it to room temperature with the furnace to obtain 8g of spinel sodium nickel manganese oxide positive electrode material with Zn replacing Mn.

[0043] 3. The comparative example adopts the same preparation method, but does not include zinc doping.

[0044] 4. Performance test and results: 1. Assemble button batteries to test the charging and discharging performance of materials.

[0045] The prepared Zn-substituted Mn spinel sodium nickel manganate positive electrode material, binder, and conductive carbon black were mixed evenly in a mass ratio of 8:1:1, and then an appropriate amount of 1-methyl-2-pyrrolidone was added dropwise to make a slurry, which was evenly coated on an aluminum foil with a thickness of about 5 mg / cm 3 , put it in the oven for drying, and then punch it out to make the positive electrode.

[0046] Using a sodium sheet as the negative electrode, the battery was assembled and tested in a glove box filled with argon.

[0047] 2. SEM analysis Figure 1 , 2 The morphology of the synthesized conventional spinel sodium nickel manganese oxide positive electrode material and the Zn-substituted Mn spinel sodium nickel manganese oxide positive electrode material precursor are shown in Figure 2. Figure 1 and 2 It can be seen that both materials are spherical, but the surface of conventional NCM particles is relatively smooth. The surface of Zn-substituted Mn positive electrode material is rougher, covered with crystalline, and its particle size is wider than the conventional particle diameter.

[0048] 3. The main properties of the embodiments and comparative examples are shown in Table 1. The discharge capacity of the spinel sodium nickel manganese oxide positive electrode material substituted with Zn in the present invention is about 135 mAh / g, and the first charge and discharge efficiency is about 85%. Compared with the general spinel sodium nickel manganese oxide positive electrode material, its capacity is increased by about 5 mAh / g. After 100 cycles, the capacity retention rate can reach about 95%, which is significantly improved. Please refer to Table 1 for specific data.

[0049]

[0050] Table 1

Claims

1. A spinel sodium nickel manganate positive electrode material in which Zn replaces Mn, characterized in that: The general structural formula of the material is: Na 0.5 Mn (1.5-x) Ni 0.5 Zn x O2, where 0<x<1.

2. The method for preparing a spinel sodium nickel manganate positive electrode material with Zn replacing Mn as claimed in claim 1, characterized in that: The following steps are involved: 1) dissolving nickel salt, manganese salt and zinc salt in deionized water to obtain a mixed metal salt aqueous solution; Dissolve sodium carbonate in deionized water, then add ammonia water to obtain a precipitant solution with a pH value of 7.5-10.5; 2) first adding a base liquid into a reaction container, and then adding the mixed metal salt aqueous solution and the precipitant solution into the reaction container for a co-precipitation reaction; After the reaction is completed, the precipitate and the supernatant are separated, and the precipitate is washed, filtered, dried, and ground to obtain a precursor; 3) The precursor and the sodium salt are uniformly mixed and then calcined. During the calcination, the temperature is first raised to 400-500° C., kept warm for 3 hours, then raised to 700-900° C., kept warm for 8-24 hours, and finally cooled to room temperature to obtain a spinel sodium nickel manganese oxide positive electrode material in which Zn replaces Mn.

3. The preparation method according to claim 2, characterized in that: The total concentration of the metal salts in the mixed metal salt aqueous solution is 1 to 2 mol / L.

4. The preparation method according to claim 2, characterized in that: The molar numbers of nickel, manganese and zinc ions in the metal salt solution are o, y and 1-oy respectively, and: 0.1<o≤1, 0.1≤y≤1, 0<1-oy≤1.

5. The preparation method according to claim 4, characterized in that The nickel salt is nickel sulfate, nickel nitrate or nickel acetate; the manganese salt is manganese sulfate, manganese nitrate or manganese acetate; the zinc salt is zinc sulfate, zinc nitrate or zinc acetate.

6. The preparation method according to claim 2 or 3, characterized in that: The concentration of sodium carbonate is 1 / 2 of the concentration of metal cations in the metal salt solution.

7. The preparation method according to claim 2, characterized in that: During the coprecipitation reaction, the temperature of the reaction system is 40-80°C.

8. The preparation method according to claim 7, characterized in that: During the coprecipitation reaction, the stirring speed in the reaction container is 200-800 r / min, the adding speed of the mixed metal salt aqueous solution is 20 ml / min-500 ml / min, and the adding speed of the precipitant solution is 20 ml / min-500 ml / min.

9. The preparation method according to claim 2, characterized in that: The base liquid is deionized water.